Letramento estocástico: uma possível articulação entre os letramentos estatístico e probabilístico - Silva, Danilo Saes Corrêa da (2018)
The growing dissemination of news, driven by social networks, makes society need to be increasingly critical. And it is within this context that Statistical Education can play an important role in the formation of this society, since it is possible for this Education to facilitate the formation of a more critical society, since the Statistical and Probabilistic Literacy help in this framing. Our general objective is to analyze which elements of Statistical Letting and Probabilistic Literacy are worked with students of the sixth year of elementary school and study the possible articulation among them through activities that involve critical posture for data analysis. During our studies we indicate how points in agrément can promote a new Literacy, the Stochastic Letters. In order to analyze how these two Literacies interact and articulate with the students, we performed an activity, based on assumptions of Didactic Engineering, which consisted in the launching addicted dice and construction of graphs to verify the relative frequency associated with each of the faces, so as to aid in the learning of Frequency Probability. To verify the critical posture of the students were inserted in the activity some addicted dice, resulting in non-equiprobable launches. The results of the activity pointed to some points in common in the Statistical and Probabilistic Literacy, such as the importance of working on Statistics and Probability concomitantly, and the relevance of working with dice, which are elements of the students' familiarity, which are the context of the students, we also indicate some difficulties encountered, such as the absence of verification of non-equipotentiality